2021
DOI: 10.3389/fsurg.2021.685155
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of <2 cm Micro-Keyhole Microvascular Decompression for Hemifacial Spasm

Abstract: Objective: Microvascular decompression (MVD) surgery has been accepted as a minimally invasive surgical modality for the treatment of hemifacial spasm (HFS). However, the size of the bone window does not match the concept of minimally invasive. This study is aimed at evaluating the efficacy and safety of &lt;2 cm micro-keyhole MVD.Methods: A total of 148 patients with HFS diagnosed in the First Affiliated Hospital of Chongqing Medical University from January 1, 2019, to July 1, 2020, who underwent MVD in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…With the advancement of microneurosurgical techniques, the size of the bone window required for MVD surgery is gradually decreasing. Studies have reported that a small bone window of about 2 cm is adequate for MVD surgery and obtains the same surgical outcomes as a large bone window [18,19]. In some institutions, a small bone flap is milled out with a milling tool and fixed with a connecting piece; in others, the bone window is enlarged with a rongeurs and repaired postoperatively with titanium mesh or other artificial bone repair material.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of microneurosurgical techniques, the size of the bone window required for MVD surgery is gradually decreasing. Studies have reported that a small bone window of about 2 cm is adequate for MVD surgery and obtains the same surgical outcomes as a large bone window [18,19]. In some institutions, a small bone flap is milled out with a milling tool and fixed with a connecting piece; in others, the bone window is enlarged with a rongeurs and repaired postoperatively with titanium mesh or other artificial bone repair material.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were routinely examined by magnetic resonance imaging (MRI)to exclude posterior fossa tumors. The surgical method has been described in detail in our previous research (Huang, Zhan et al 2021). What needs a special explanation is that we used a <2 cm micro-Keyhole to complete the operation.…”
Section: Patientsmentioning
confidence: 99%